The Role Of Human Resource Management in Improving the Health Performance at the Malahayati Islamic Hospital Medan In 2024 - Cahya Aisyah Daulay (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Human resource management that has been applied in the management of the Islamic Malahayati Hospital is very good so that the Islamic Malahayati Hospital gets a different assessment compared to other hospitals in Medan which implemented the integrated ISO 9001;2008 management system. This study aims to determine how the existing resource management in the Islamic Malahayati Hospital. This type of research is a quantitative study with a cross-sectional study approach. The population in this study were all nurses at Islamic Malahayati Hospital as many as 190 civil servant nurses with a sample of 129 people. The sampling technique in this study used proportional random sampling. Data analysis was performed by univariate, bivariate with chi-square test and multivariate analysis with logistic regression. There is a relationship between recruitment and selection (p-value = 0.000), training and promotion (p- value 0.000), job appraisal, and salary management (p values = 0.000), with the performance of nurses at the Islamic Malahayati Hospital. Promotion and training have the greatest relationship with nurse performance with an OR value of 15,934. It is recommended to the hospital to increase the training and promotion of health workers, especially by involving more employees, in this case, nurses in training activities or increasing their capacity, and it is necessary to have a promotion or increase in positions that are in accordance with the work of nurses so that nurses are more active and more motivated in improving their performance while working in the hospital.